Profitabilitas Pengaruh Perputaran Kas Dan Perputaran Piutang : Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Puspita, Zhilvia Della; Lisiantara, G. Anggana (Jurnal Riset Akuntansi Politala, 2024)
This study aims to determine the effect cash turnover, account receivable turnover, and profitability in manufacturing consumption companies listed on the Indonesia Stock Exchange. The purpose of this studies is to examine relation influence cash turnover, receivable turnover on the profitability of manufaturing companies in the consumer goods industry secrot in the Indonesia Stock Exchange for the period of 2020-202. 1In this study, samples were taken at manufacturing companies listed on the IDX in the period 2020 – 2022 using the purposive sampling method. The relationship or influence of variables is explained using multiple regression methods with the data processing in this research is the classical assumption test, autocorrelation test, multiple linear test, t test, F test, coefficient of determination. The result of the analyzes show that the influence of cash turnover and account receivable turnover on profitability on manufacturing companies in the food and beverage sub-sector consumption sector partially or simultaneously.